HIV medicine as double-sided sword: care and prevention. (19th April 2018) - Han, Win M; Ohata, Pirapon J; Nanthapisal, Kesdao; Ruengpanyathip, Chavalun; Sattayamong, Pornwinit; Avihingsanon, Anchalee; Puthanakit, Thanyawee; Gatechompol, Sivaporn; Hiransuthikul, Akarin; Kerr, Stephen J; Ramautarsing, Reshmie; Ubolyam, Sasiwimol; et al.
The 20th Bangkok International Symposium on HIV Medicine Queen Sirikit National Convention Centre, Bangkok, Thailand, 17–19 January 2018. The HIV Netherlands Australia Thailand research collaboration (HIV-NAT) convened the 20th Bangkok Symposium on HIV medicine. The symposium, considered one of the most comprehensive clinical conferences on HIV in the Asia Pacific region, is held annually in January. The 2018 symposium was the second year straight in which the sessions were live webcast via the internet. The highlights of this year's sessions included prevention for HIV, the potentials for an end to HIV, management of hepatitis C infection, and a special session on same-day ART initiation.